Khitobah and Arabic Debate Courses for Strengthening Speaking Skills - Hermiwati Hermiwati; Faisal Mahmoud Adam; Zakiya Arifah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Based on observations, several Arabic language education students at the University of Jambi are graduates of public schools or non-religious educational institutions, so they lack a strong foundation in Arabic and require intensive programs to help them master speaking skills. The purpose of this study is to describe the process of learning maharah kalam and analyze the forms of learning in the continuing course of khitobah wal mundzarah as a strategy to strengthen the maharah kalam of Arabic Language Education students at the University of Jambi. The research method used is a qualitative approach with a case study type of research. This research was conducted by starting with observation and using structured interviews. Interviews were conducted with 5 students and 2 lecturers of the course as research samples. Then, the data obtained was analyzed using the Miles and Huberman and Saldana data analysis model, which includes the stages of data condensation, data presentation, and conclusion drawing. The results of the study show that the Arabic language learning process in the khitobah wal munadzarah course is carried out in stages, starting from theory, guided practice, practice, and output. The form of khitobah learning includes basic khitobah theories such as speech structure, speaking ethics, speech practice or public rhetoric, and conference/seminar simulations (students presenting papers or ideas in front of the class). Meanwhile, the munadzarah learning form consists of role-playing (students acting as orators or resource persons in certain scenarios), structured discussions with clear rules for constructing arguments, argument delivery exercises, and a final project in the form of an Arabic debate.